EFFICACY OF BLADDER TRAINING PROCEDURE IN PATIENTS UNDERGOING TURP - Harimurti, Nicolaus Kresno; Ali, Zulfikar; Utomo, Trisula (Indonesian Journal of Urology, 2018)
Objective: Catheter management is conducted to the patients undergoing transurethral resection of the prostate (TURP). There were many arguments between clinical practitioners about bladder training procedure after TURP procedure. This study aims to determine whether there is a relationship between bladder training action and success of spontaneous micturition in post TURP procedure in patients with urinary retention caused by prostate enlargement. Material & methods: Randomized clinical trial was conducted at Kardinah General Hospital, Tegal from October 2015 to February 2016. 44 study participants who underwent TURP were randomly allocated into two groups. In Group I, patient’s Folley catheter was clamped prior to its removal (bladder training group); and in Group II was not clamped (control group). Results: Mean age of patients was 64.48 ± 8.1 years old. There were 23 patients (52.3%) have had history of recurrent urinary retention and 21 patients (47.7%) have had not (p=0.560). There were 4 patients (17.4%) in Group I and 1 patient (4.7%) in Group II who required re-catheterization and discharge with catheter. There was no statistically significant difference in spontaneous micturition rate between bladder training group and control group (p=0.187).  Conclusion: The result of the current study identified that bladder training to patients undergoing TURP procedure had no significant impact in spontaneous micturition.